2009
DOI: 10.1002/bjs.6722
|View full text |Cite
|
Sign up to set email alerts
|

Non-viral Smad7 gene delivery and attenuation of postoperative peritoneal adhesion in an experimental model

Abstract: Ultrasound-microbubble-mediated gene transfection provides timely targeted gene delivery for the treatment of postoperative peritoneal adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…Our study demonstrates that the frequently used HKG, that is, GAPDH, is not suitable for normalization of adhesion tissue and therefore could account for the variation of results obtained by these studies (21)(22)(23). Our study shows that GAPDH expression is unstable across tissue types, a finding that is consistent with other studies (24).…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrates that the frequently used HKG, that is, GAPDH, is not suitable for normalization of adhesion tissue and therefore could account for the variation of results obtained by these studies (21)(22)(23). Our study shows that GAPDH expression is unstable across tissue types, a finding that is consistent with other studies (24).…”
Section: Discussionsupporting
confidence: 91%
“…Prevention is a far more desirable goal (Gomel et al, 1996;Mettler, 2003;Scott-Coombes et al, 1993), and much effort has been expended on adhesion prevention using various chemical compounds and barriers (Corrales et al, 2008;Guo et al, 2009;Ilbay et al, 2004;Kutlay et al, 2004;Mettler et al, 2003;Oncel et al, 2004). Systematic reviews of these treatments have reported that none consistently prevent adhesion formation (Kumar et al, 2009;Metwally et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…No satisfactory solution has proved to ameliorate peritoneal fibrosis efficiently. Recent studies have shown that the recovery of surgically damaged mesothelium reduces the peritoneal adhesions and fibrosis, resulting in improved structural repair and function of peritoneum [6], [8]. Therefore, promoting the mesothelial recovery may be a novel therapeutic target to reduce peritoneal fibrosis.…”
Section: Introductionmentioning
confidence: 99%